Schooling, inequality and government policy - Oleksiy Kryvtsov; Alexander Ueberfeldt (Bank of Canada, 2007)
This paper asks: What is the effect of government policy on output and inequality in an environment with education and labor-supply decisions? The answer is given in a general equilibrium model, consistent with the post 1960s facts on male wage inequality and labor supply in the U.S. In the model, education and labor-supply decisions depend on progressive income taxation, the education system, the social security system, and technology-driven wage differentials. Government policies affect output and inequality through two channels. First, a policy change leads to an asymmetric adjustment of working hours and savings of schooled and unschooled individuals. Second, there is a redistribution of the workforce between schooled and unschooled workers. Using a battery of proposed government policies, we demonstrate that skill redistribution dampens the response of wage inequality to a policy change and amplifies the response of output by an additional 1 to 2 percent.
Keywords: H52; J31; J38; 330; Labour markets; Potential output; Productivity; Politische Entscheidung; Bildungsverhalten; Arbeitsangebot; Soziale Ungleichheit; Wirkungsanalyse; USA